Diversity and ecological roles of macrofungi within UiTM Jengka, Pahang, Malaysia - Mat Shah Fee, Nur Amirah Sakinah; Mohd. Izam, Nur Amalina; Farinordin, Farah Ayuni; Azuddin, Nurul Farizah; Rosli, Hafizi; Ismail, Nor Azliza (Universiti Teknologi MARA (UiTM), 2023)
Macrofungi in urban areas are rarely explored, although their existence may significantly impact the ecosystem of these non-forested habitats. Therefore, early macrofungal documentation was carried out on the UiTM Pahang campus to record species diversity and their ecological roles in urban areas. Fruiting bodies of macrofungi were collected and documented from selected sites within the campus areas and were preserved as voucher specimens. Specimens were identified using main macro- and micromorphological key characters and other important features such as odour and colour change upon bruising. A total of 62 species representing two phyla and 23 families were collected in this study. Basidiomycota dominated the campus areas with 54 species, while Ascomycota appeared the least with only eight species. Numerous saprophytic fungi and a small number of mycorrhizal and parasitic fungi living within the campus areas were recovered. The majority of the macrofungi played a role as saprophytes (46 species; 74%), followed by mycorrhiza (14 species; 23%) and parasites (two species; 3%), displaying a balanced proportion of saprophytic and mycorrhizal fungi with extremely low parasitic fungi. The findings also clearly demonstrated that UiTMCPh is a good habitat for numerous groups of macrofungi and is highly favoured by saprophytic macrofungi. Considering the high diversity of macrofungal species from the current work, conducting extensive sampling and regular monitoring of macrofungi are necessary to enhance the conservation programs on the campus.